Avaliação da viabilidade técnico-econômica de projetos de geração eólica no Brasil - Cruz, Ulysses de Brito (2013)
Wind power is very relevant not only for being a clean and renewable power source, but also for being financially viable. Mindful of this scenario, Brazil has been searching to diversify its power matrix with the use wind power on a large scale as a sustainable alternative source of power. Brazil s climate and topography contribute to keeping the concentration of winds. Furthermore, the complementary function of wind power and the cutting on average production costs are the main financial attractiveness compared to hydropower and other sources, bringing new investors. The first step was the building of a new sector regulatory model, it was not enough though. Technical, contractual, environmental, regulatory and government barriers have to be eliminated or reduced. Recent data from ANEEL show that by 2015 will be expected to come into operation in Brazil 8579.45 MW of wind power. However, from that amount, only 27,17% of the projects are environmentally certified and with their construction schedule on time. Most projects (72,83%) have problems concerning not started, delayed and suspended works due to lack of environmental license, request to revoke authorization, litigation and environmental statement infeasibility of the project. This work attempts to investigate the aspects related to the technical-economic feasibility of wind power projects in Brazil, with the aid of RETScreen4 program, presenting solutions which eliminate or reduce the most commonly identified barriers, aiming at contributing to setting wind source in the Brazilian matrix energy.